Sistem Informasi Geografis Pemetaan Wilayah Penyalahgunaan Narkoba Mengunakan Metode SOM (Self-Organizing Map) Studi Kasus: Kabupaten Aceh Tenggara - Alkhalidi, Muhammad Waly; Nadeak, Berto; Sayuthi, Muhammad (Building of Informatics, Technology and Science (BITS), 2020)
Geographic Information System is an information system that is used to enter, store, recall, process, analyze, and produce data on geographic or geospatial reference, to support a decision and planning process. With the existence of a geographic information system it will be easier for decision makers to know the mapping of the number of drug abuse areas in the Southeast Aceh Regency. Because with the existence of GIS, it will be illustrated the mapping of the number of drug abuse areas in Southeast Aceh in actual conditions. In this study, Self-Organizing Maps (SOM) was used as a method to determine the grouping of data on drug abuse areas. Self-Organizing Maps (SOM) contains layers that will arrange themselves based on input certain values ​​in a group known as clusters. Thus the learning process of the Self Organizing Map algorithm forms 4 clusters with different characteristics in each cluster and has different colors in each cluster. Furthermore, the system implementation utilizes ArcGIS 10.1. The results of this study are an illustration of the mapping of drug abuse areas in the Southeast Aceh district that can provide information about the area of ​​drug abuse in the Southeast Aceh District